MEDIASI DALAM PENYELESAIAN SENGKETA KEWARISAN DI PENGADILAN AGAMA MAKASSAR KELAS I A - Devi Wardan Sari; Alimuddin; Ibnu Izzah (Universitas Islam Negeri Alauddin Makassar, 2023)
Abstract The main issue is mediation in the sttlement of inheritance disputes at the Makassar Religious Court Class I A, the subject matter is divided into three sub-problems, namely: 1) How is the ,ediation process in the sttlement of inheritance disputes in PA Makassar Class IA. 2) What is the role of the mediator in the sttlement of inheritance disputes in PA Makassar Class IA. 3) What are the results of mediation in the settlement of inheritance disputes in PA Makassar Class IA. The type of research is descriptive qualitative, namely field research, using a normative juridical and empirical juridical approach with interview and documentation data collection methods. Based on the results of the study, it shows that the mediation process is divided into three stages, namely, the pre-mediation stage, the mediation process stage, and the final stage of implementation. The prsence of he parties is very important for the continuation of the mediation. The mediator must be equipped with psychological knowledge in addition to psychological knowledge of law. The succes in the mediation in the settlement of inheritance disputes at the Makassar Religious Court Class IA is still less effective, as for the causes of the low result obtained, one of which is the complexity of an inheritance case, the obligation to present parties who are not only two or three but can be more than that. The implication of the research is that the mediation process is very important for the mediator to provide a sense of security, peace, and peace to the parties. The mediator must improve the ability to mediate the parties, namely not only from the rules but also the ability to dialogue with the parties. The good faith of the parties is also very influential on the success of the mediation, that is, it is hoped that the partis can regenerate good relations and undergo the mediation process in good faith.